Tradisi Baarak Naga dalam Proses Perkawinan di Kelurahan Ulu Benteng Kecamatan Marabahan Kabupaten Barito Kuala - Khairullah, Muhammad Fajar; Mardiani, Fitri (Lambung Mangkurat University, 2021)
The Baarak Naga tradition which is held in Ulu Benteng Village, Marabahan District, Barito Kuala Regency is a hereditary tradition for residents who have a dragon lineage when they are about to get married. This tradition only exists in Ulu Benteng Village, where the majority of the population is the Bakumpai Dayak Tribe. However, as the times progressed, this tradition began to be rarely carried out only a few times a year. This study intends to determine the origin and process of implementing the dragon Baarak tradition in Ulu Benteng Village, Marabahan District. The method used in this study uses the historical method which has several stages, namely Heuristics, Criticism, Interpretation and Historiography. The first stage is Heuristics or data collection. The data was obtained through primary sources, namely direct interviews with the descendants of the owners and custodians of the dragon's head as well as residents who have carried out this tradition. While secondary data can be obtained through books, scientific journals, articles on the internet and direct observations of research. After receiving the data, the next stage is criticism, both external criticism and internal criticism. The data that is criticized goes back to the Interpretation stage and ends with the historiography or writing stage. The results showed that the Baarak Naga tradition existed more than 100 years ago as a form of respect for their ancestors and asking for blessings so that the marriage process runs smoothly and safely